Causas frecuentes de devolución de productos farmacéuticos al almacén de una Droguería, durante el periodo mayo 2018 – abril 2019 - García Caballero, Vilma Jhovana (2019)
The present work the causes of the pharmaceutical products returned to a Drugstore, the destination of these returned products and the corrective measures before the client are evaluated. The study was carried out by means of a descriptive, transversal and retrospective design, based on a procedure for the drugstore. According to what we work, the sample of the cause of return with the highest percentage is for surplus merchandise (32%), followed soon by expiration (23%), billing error (16%), failure of origin (14%), product in poor condition (11%) and finally by health alert (5%). Regarding the destination of returned products, 48% were admitted to the Approved Area, followed by the Area of Exchanges and Returns (41%) and in the third place to the Area of Losses and Refusals (11%). As for corrective measures, 84% of all returned products were resolved through the respective exchange, while 16% was generated credit note. This way, the procedures of the services (PDEs) proper of the Droguería are complied with